The effect of impact exercises and electrical stimulation upon certain anaerobic lactational ability and upon the skill of smashing in badminton for advanced female players. - Lect. Dr. Nizar Faeq Saleh; Aya Kamran Abdullah; Prof. Dr. Shaima Rashid Taan (Zien Journals, 2022)
The research aims at detecting the impact of exercises with electrical stimulation on the anaerobic ability and the skill of smashing for advanced badminton players as well as the effect of impact exercises without electrical stimulation on anaerobic ability and smashing skill for badminton female players. The experimental approach adopted the two equal experimental groups on a sample of (8) advanced badminton players in Kirkuk Governorate, distributed to the clubs of (Sulaf Sports and K-1 Sports), participating in the sports season (2021-2022). After defining the tests and experimentation for (8) consecutive training weeks, (3) units a week to enhance the muscular extension that produces the explosive ability of the legs and arms by making use of training tools suitable for the specifics of female badminton players. With regard to the direction of muscle contractions, emphasis was directed to the function of the key muscle groups identified as being necessary to accomplish this ability. These muscle groups are similar to their motor pathways. One training unit EMS (Electrical Muscular Stimulation) lasts for 10 to 15 minutes. As for the frequencies used during electrical stimulation, they depended on the gradient from 150 Hz to 250 Hz. After completing this experiment, the results were processed by using (SPSS) system to form conclusions and applications. Applying the impact training and electrical stimulation contributes to developing the anaerobic and nonlactic ability. As they work to build and strengthen each of them, advanced badminton players who exercise with trainings without electrical stimulation can increase their forward smashing abilities. When experienced badminton players use training and electrical stimulation, it will be vital to pay attention to the use of joint physiological testing in the lab to monitor their training state.
Keywords: Impact training; electrical stimulation; anaerobic lactic ability; badminton